Risk Disclosure in Indonesian Banking: The Role of Board of Directors and Institutional Ownership - Dhea Vania Dominique Pijoh; Bima Cinintya Pratama; Hadi Pramono; Ira Hapsari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine risk disclosure by considering the influence of board tenure, gender composition of female board of directors, and institutional ownership. This study used a purposive sampling method at commercial banks registered with OJK in a total of 205 samples with 41 banking companies during the 2017-2021 period. To test the research hypothesis used panel data regression model analysis. The analysis techniques used in this study were descriptive statistical tests, preliminary tests (Breusch-Pagan, likelihood tests, hausman tests), diagnostic tests (heteroscedasticity tests and autocorrelation tests), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study will use the fixed effect model to examine the relationship between variables in the regression model 1. The results of the analysis prove that board tenure and institutional ownership have a positive effect on risk disclosure, while the gender composition of female directors has no effect on risk disclosure.